Clinical Study to Analyze the Intramuscular Anatomy of Musculocutaneous Perforators of Anterolateral Thigh Flaps - Renganathan, Gopi; Karthikeyan, G.; Vishwanath, Gurusamy; Singh, S.K.; Venkatnaryanan, R. (Journal of Reconstructive Microsurgery, 2017)
Background Anterolateral thigh (ALT) flap is a common flap used for many microsurgical reconstructive procedures. Majority of these flaps are based on the musculocutaneous perforators, which, after arising from source artery, course through the bulk of the vastus lateralis muscle. The vascular anatomy of the ALT flap has been often decried as its limiting factor.Methods In this prospective study conducted over 3 years, 207 cases of ALT flap were evaluated. During the harvest of ALT flap, musculocutaneous perforators were laid open through the vastus lateralis, and its variations and pattern were studied for clinical anatomy as well as impact of anatomy on the viability of the flap postoperatively.Results The perforators were recognized to be grouped into three broadly distinguishable anatomical patterns: linear (I), branching (Y), or tortuous (S). While the majority of perforators (51%) were linear “I” perforators, serpentine “S” and branching “Y” perforators were 28 and 21%, respectively. The clinical outcomes were also related to the simplicity of these perforators course as linear “I” perforators had 100% flap viability.Conclusion During the harvest of 207 ALT flaps through 3 years, it could be deciphered that the musculocutaneous perforators traverse through the bulk of vastus lateralis muscle in only three types of patterns (IYS pattern). This identification of pattern could help in prevention of injury while delineating the perforators. Identification and typing of anatomical variation of the musculocutaneous perforator within the vastus muscle could lead to a predictable and safer harvest of the ALT flap.
Keywords: musculocutaneous perforators; anatomical variations; IYS pattern